PENGARUH PENGELOLAAN MODAL KERJA, KESEMPATAN BERTUMBUH, UKURAN PERUSAHAAN, KEPEMILIKAN INSTITUSIONAL TERHADAP KINERJA KEUANGAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Leni Setryaningsih, 12.05.52.0106; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2016)
This study aims todetermine the effectof working capital management, growth opportunities, company size, institutional ownership, the financial performance. The populationin this research ismanufacturing companies listedin Indonesia Stock Exchange 2012-2014 year The sample was taken by purposive sampling method. Data were analyzed using skewness-kurtosis normality test, classic assumption test, koofisien determinasi test, F test and test hypotheses. The test results working capital variables are significant positive effect on the performance of financial , growth opportunities variables significant positive effect on the performance of financial, company sizevariables significant negative effect on the performance of financial, institutional ownership variable statistically not significantpositive effecton the performance of financial.Keywords: Working Capital, Growth Opportunities, Company Size, Institutional Ownership, The Performance Of Financial